Constitutional Right or Privilege to Participate in Extracurricular Activities: Editor: Thomas H. Sawyer. Issue 9 (21st November 2020) - Sawyer, Tonya L.
Abstract : This article looks at an age- and gender-discrimination case that was filed based on a high school soccer player who was cut from varsity and was deemed too old to play for the junior varsity team.